The functional responses of phosphate-deficient lupin nodules as mediated by phosphoenolpyruvate carboxylase and altered carbon and nitrogen metabolism - Kleinert, Aleysia (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Plant biotechnology))--University of Stellenbosch, 2010.